Ramipril reduces incidence and prolongates latency time of radiation-induced rat myelopathy after photon and carbon ion irradiation - Saager, Maria; Hahn, Eric W.; Peschke, Peter; Brons, Stephan; Huber, Peter E.; Debus, Jürgen; Karger, Christian (Journal of radiation research, 2020)
To test the hypothesis that the use of an angiotensin-converting enzyme inhibitor (ACEi) during radiotherapy may be ameliorative for treatment-related normal tissue damage, a pilot study was conducted with the clinically approved (ACE) inhibitor ramipril on the outcome of radiation-induced myelopathy in the rat cervical spinal cord model. Female Sprague Dawley rats were irradiated with single doses of either carbon ions (LET 45 keV/μm) at the center of a 6 cm spread-out Bragg peak (SOBP) or 6 MeV photons. The rats were randomly distributed into 4 experimental arms: (i) photons; (ii) photons + ramipril; (iii) carbon ions and (iv) carbon ions + ramipril. Ramipril administration (2 mg/kg/day) started directly after irradiation and was maintained during the entire follow-up. Complete dose-response curves were generated for the biological endpoint radiation-induced myelopathy (paresis grade II) within an observation time of 300 days. Administration of ramipril reduced the rate of paralysis at high dose levels for photons and for the first time a similar finding for high-LET particles was demonstrated, which indicates that the effect of ramipril is independent from radiation quality. The reduced rate of myelopathy is accompanied by a general prolongation of latency time for photons and for carbon ions. Although the already clinical approved drug ramipril can be considered as a mitigator of radiation-induced normal tissue toxicity in the central nervous system, further examinations of the underlying pathological mechanisms leading to radiation-induced myelopathy are necessary to increase and sustain its mitigative effectiveness.